Study of M23C6 precipitation in a 45Ni-35Cr-Nb alloy - Sosa Lissarrague, Matías Humberto (2019)
The 45Ni-35Cr-Nb alloy, commonly known as ET45 micro, produced in the form of centrifugally cast tubes, was studied by means of optical microscopy after aging treatments at 1073 and 1173 K for different times. A description of M23C6 secondary carbides precipitation phenomenon was made as a function of time. The purpose of carrying out a kinetic study of the precipitation of this phase is to be able to calculate the activation energy required for secondary precipitation. This allows to infer what is the mechanism associated with it. Analysis after using the Johnson-Mehl-Avrami-Kolmogorov (JMAK) model showed that secondary carbide precipitation occurs in a single stage. It was found that this phenomenon, which is assisted by diffusion, has an activation energy of 196 kJ/mol. This value would indicate that the diffusion of Cr atoms in the austenitic matrix is the phenomenon that dominates the precipitation of the M23C6 secondary carbide.